A preparation method of PVC composite heat stabilizer, paste resin and building materials

By using PVC composite thermal stabilizers prepared by using materials such as montmorillonite, stearic acid, calcium chloride, zinc chloride and silane coupling agents, the problem of poor thermal stability of PVC building materials is solved, and higher thermal stability and lower environmental pollution are achieved.

CN119161636BActive Publication Date: 2025-04-22ZHEJIANG HAILIDE NEW MATERIAL
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411676164.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-22
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Existing PVC building materials have poor thermal stability and are prone to decomposition under high temperature or sun exposure, producing hydrogen chloride gas, resulting in unstable product quality and environmental pollution.

Method used

PVC composite heat stabilizer is prepared by materials such as montmorillonite, stearic acid, calcium chloride, zinc chloride and silane coupling agent. By layering modification and connection of calcium stearate/zinc and silane modification groups, the thermal stabilization effect of the heat stabilizer is improved.

Benefits of technology

It significantly improves the thermal stability of PVC building materials, reduces the generation of HCl gas, avoids the "zinc burning", improves product quality and production efficiency, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the technical field of PVC building materials, and specifically relates to a preparation method of a PVC composite heat stabilizer, a paste resin and a building material. The PVC composite heat stabilizer is obtained by grinding and coupling agent expansion modified sodium montmorillonite, and grafting calcium zinc stabilizer, and has higher thermal stability and other effects on PVC. The PVC paste resin is made by mixing PVC, plasticizer, PVC composite heat stabilizer, liquid flame retardant and anti-ultraviolet agent, and the process is simple and easy to promote. The PVC building material is made by adjusting the viscosity of PVC paste resin, coating with polyester substrate and heating and fusing, and has better thermal stability and strength, is suitable for use as a building material, is conducive to improving production efficiency and product quality, solves the defects of traditional stabilizers such as "zinc burning", and improves the thermal stability of building materials, reducing production costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of PVC building materials, and particularly relates to a preparation method of a PVC composite heat stabilizer, a paste resin and a building material. Background Art

[0002] Building materials are the most important component of span space structures and are widely used in large public facilities, such as roof systems of stadiums, airport halls, exhibition centers, platforms, landscape pavilions, etc. Usually, such building materials are made of a polyester substrate coated with a PVC (polyvinyl chloride) layer. PVC building materials have great development prospects due to their excellent properties such as light weight, high strength, flexibility, and uniform light transmittance. Since most of the application scenarios are outdoors, thermal stability has become a very important product indicator, and it is difficult to achieve such requirements by adding general stabilizers. PVC itself has an amorphous structure, a small degree of branching, and poor stability to light and heat. It will decompose and produce hydrogen chloride when it is above 100°C or exposed to sunlight for a long time; during the production process, it will manifest as a large number of bubbles on the surface and inside of the product, affecting the product quality. In order to ensure normal production, it is necessary to apply in small quantities and multiple times in steps, which increases production costs and makes product quality unstable.

[0003] In order to solve the problem of PVC building material stability, most PVC building material manufacturers will choose to add stabilizers on the original basis. Stabilizers can prevent PVC from degrading during processing and use. Traditional stabilizers are mainly used to capture free radicals generated during PVC degradation, thereby preventing further degradation of PVC. Commonly used PVC heat stabilizers include montmorillonite, stearic acid soap heat stabilizers, etc. For example, patent documents CN109851954A, CN112724558A, etc. all use a method of mixing multiple heat stabilizers as PVC heat stabilizers.

[0004] Due to the use of mixed heat stabilizers, the stability of PVC products and production processes under traditional methods has not changed fundamentally, and stability problems still exist. In addition, the traditional zinc soap salt PVC stabilizer will promote the dehydrochlorination of PVC during the action process, causing PVC to degrade in a short period of time, resulting in "zinc burning", reducing production efficiency, and causing pollution to the environment. Summary of the invention

[0005] In view of the problem that existing PVC building materials have poor thermal stability, the purpose of the present invention is to provide a preparation method of a PVC composite thermal stabilizer, a paste resin and a building material.

[0006] In the first aspect, the present invention provides a method for preparing a PVC composite heat stabilizer, wherein the PVC composite heat stabilizer is prepared from montmorillonite, stearic acid, calcium chloride, zinc chloride, and a silane coupling agent, and the preparation method comprises the following steps:

[0007] S1: montmorillonite is dispersed and swelled with purified water to obtain a montmorillonite dispersion; the montmorillonite dispersion is ground, stearic acid is added during the grinding, and the grinding is performed to obtain a pre-modified montmorillonite dispersion;

[0008] S2: taking a silane coupling agent and adding pure water to hydrolyze it to obtain a silane coupling agent liquid; heating the silane coupling agent liquid, adding a calcium chloride / zinc chloride mixture to blend, and obtaining a silane coupling agent / calcium chloride / zinc chloride dispersion;

[0009] S3: Blending the silane coupling agent / calcium chloride / zinc chloride dispersion and the pre-modified montmorillonite dispersion, heating and reacting to obtain a PVC composite heat stabilizer;

[0010] Preferably, in step S1, the montmorillonite is ground to an average particle size of 200nm-400nm; in step S2, the hydrolysis temperature is 20°C-30°C, and the hydrolysis time is 2h-4h; in step S2, the silane coupling agent liquid is heated to 90°C-100°C and the calcium chloride / zinc chloride mixture is added for blending; in step S3, the heating reaction temperature is 90°C-100°C, and the reaction time is 2h-4h.

[0011] Preferably, the montmorillonite is sodium-montmorillonite.

[0012] Preferably, in step S1, the amount of stearic acid added is 1 to 4 times that of montmorillonite, calculated by weight.

[0013] Preferably, in step S1, the amount of purified water added is 10 to 20 times that of montmorillonite in parts by weight;

[0014] Preferably, in step S1, the montmorillonite dispersion is prepared by mixing and stirring in an emulsifier at a speed of 10000 rpm to 20000 rpm for 10 min to 30 min.

[0015] Preferably, in step S1, the montmorillonite is ground to an average particle size of 200 nm to 300 nm.

[0016] Preferably, in step S2, the total amount of calcium chloride and zinc chloride is 1 to 4 times that of montmorillonite, calculated by weight ratio. Calcium chloride and zinc chloride can be commercially available blends, and the ratio of calcium chloride to zinc chloride belongs to conventional techniques in the art and can be conventionally varied.

[0017] Preferably, in step S2, the amount of the silane coupling agent added is 0.1 to 0.4 times that of the montmorillonite in parts by weight.

[0018] Preferably, in step S2, the silane coupling agent is at least one of KH550 (γ-aminopropyltriethoxysilane) and KH560 (γ-glycidyloxypropyltrimethoxysilane).

[0019] In the aforementioned PVC composite heat stabilizer, when the montmorillonite is sodium-based montmorillonite, it has good in-situ polymerization plasticity, expansion, cation exchange, dispersibility and thermal stability, which is conducive to grinding and dispersing modification. Using pure water to swell the montmorillonite is conducive to grinding with a sand mill to reduce the particle size of the montmorillonite and increase the interlayer spacing. In step S1, the stearic acid is used for modification while grinding, which is conducive to the ion exchange reaction, wherein the hydrogen ions (H + )It is easy to replace the metal ions between the montmorillonite layers, increase the interlayer distance between the montmorillonite layers, increase the specific surface area, and enhance the activity. Stearic acid reacts with montmorillonite to obtain stearic acid modified montmorillonite. Zinc stearate can absorb the byproduct HCl gas in the PVC system, and calcium stearate can inhibit the occurrence of the "zinc burning" phenomenon. Calcium stearate / zinc modified montmorillonite is beneficial to improve the long-term stability of PVC film. The modification of silane coupling agent further improves the thermal stability effect of the heat stabilizer.

[0020] In the second aspect, the present invention provides a PVC paste resin which can be used for PVC coating of PVC building materials. The PVC paste resin contains the following materials (also referred to as raw materials): 100 parts by weight of PVC, 30-70 parts by weight of plasticizer, 10-15 parts by weight of liquid flame retardant, 1-3 parts by weight of anti-ultraviolet agent, and 1-4 parts by weight of the aforementioned PVC composite heat stabilizer.

[0021] Preferably, the preparation method of the PVC paste resin comprises the following steps: mixing PVC, a plasticizer, a liquid flame retardant, an anti-ultraviolet agent, and a PVC composite heat stabilizer, and stirring to obtain a PVC paste resin;

[0022] Preferably, the plasticizer is at least one of DINP (diisononyl phthalate), DOTP (dioctyl terephthalate), DOP (dioctyl phthalate), and DOA (dioctyl adipate);

[0023] Preferably, the liquid flame retardant is at least one of tricresyl phosphate, toluene diphenyl phosphate, and triphenyl phosphate;

[0024] Preferably, the anti-ultraviolet agent can be selected from at least one of UV-531 and UV-9;

[0025] A third aspect: The present invention provides a PVC building material, which can be used as a building material (such as a building membrane material). The building material is made of a polyester substrate and a PVC coating, and the preparation method thereof comprises the following steps:

[0026] The aforementioned PVC paste resin is added with a viscosity reducer to adjust the viscosity on the machine to obtain a PVC slurry; the PVC slurry and the polyester substrate are dipped and coated through the roller of a coating machine; after the coating is completed, it is heated and fused with the PVC film to obtain a PVC building material.

[0027] Preferably, the viscosity reducer is at least one of the D series solvent oils, and more preferably D80 solvent oil.

[0028] Preferably, the viscosity of the PVC slurry on the machine is 1000 mpa.s to 2000 mpa.s.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) The PVC composite heat stabilizer of the present invention is modified by composite modification, the montmorillonite is expanded and modified, and calcium / zinc stearate and silane modification groups are connected, so that the heat stabilization effect of the heat stabilizer on PVC is improved, the generation of HCl gas by-products is reduced, and the "zinc burning" phenomenon of traditional metal soap stabilizers during processing is avoided, thereby improving product quality, reducing environmental pollution, and improving production efficiency, which is in line with the green and environmentally friendly production concept.

[0031] (2) The PVC composite heat stabilizer of the present invention can prevent PVC from being degraded during processing and use, thereby extending the service life of the product and improving the performance and reliability of the product.

[0032] (3) The PVC paste resin and PVC building materials of the present invention have a simple preparation method and readily available raw materials, which reduces the production cost of PVC building materials and has good economic benefits.

[0033] (4) The PVC building material of the present invention has high stability, excellent physical and chemical properties, such as good flame retardancy and high mechanical strength, and can be widely used in the construction, medical, electronic and electrical industries, and has broad application prospects;

[0034] In general, compared with the prior art, the present invention not only improves the product quality and performance of PVC building materials, but also reduces production costs and environmental pollution, and has significant advantages. DETAILED DESCRIPTION

[0035] The present invention will be further described below in conjunction with specific embodiments. The embodiments are merely regarded as illustrative descriptions of the technical solutions of the present invention and are not regarded as limiting the protection scope of the present invention.

[0036] The materials and sources in the following examples are as follows:

[0037]

[0038] Example 1: Preparation of a novel PVC composite heat stabilizer and PVC building materials

[0039] Preparation of a new type of PVC composite heat stabilizer:

[0040] (1) 5g of sodium montmorillonite and 95g of pure water were fully mixed and emulsified by an emulsifier to obtain a montmorillonite aqueous dispersion (mixed and stirred at 15000rpm for 20min) to fully swell the montmorillonite. The obtained montmorillonite aqueous dispersion was transferred to a sand mill and ground at 3500rpm and 60rpm for 5h. After grinding for 2h, 10g of stearic acid was added to the system for online modification. The grinding was continued until the average diameter of the montmorillonite particles was 250±20nm to obtain a pre-modified montmorillonite dispersion;

[0041] (2) 1 g KH550 was mixed with 2 g pure water, and hydrolyzed in a constant temperature water bath at 25 °C for 2 h to obtain a silane coupling agent liquid. After the temperature was raised to 95 °C, 15 g of a calcium chloride / zinc chloride mixture was added and mixed in an oil bath for 3 h to obtain a silane coupling agent / calcium chloride / zinc chloride dispersion;

[0042] (3) blending the silane coupling agent / calcium chloride / zinc chloride dispersion obtained in step (2) and the pre-modified montmorillonite dispersion obtained in step (1), and reacting them in an oil bath at 97° C. for 4 h to obtain a PVC composite heat stabilizer;

[0043] Preparation of a PVC building material:

[0044] (1) 100 g of PVC resin, 40 g of DINP, 10 g of DOA, 3 g of PVC composite heat stabilizer, 10 g of tricresyl phosphate, and 1 g of UV-531 were mixed and beaten to obtain PVC paste resin; the viscosity of the obtained PVC paste resin was adjusted to a viscosity of 1500 mPa.s on a machine using a viscosity reducer D80 to obtain PVC slurry;

[0045] (2) The PVC slurry and mesh prepared in step (1) are dipped and coated by the roller of a coating machine. After coating, the PVC slurry and mesh are fused with the PVC film at a high temperature of 180° C. to obtain a PVC coated product (i.e., PVC building material, which can be used as PVC architectural membrane material).

[0046] Example 2: Preparation of a novel PVC composite heat stabilizer and PVC building materials

[0047] Preparation of a new type of PVC composite heat stabilizer:

[0048] (1) 8g of sodium montmorillonite and 92g of pure water were fully mixed and emulsified by an emulsifier to obtain a montmorillonite aqueous dispersion (mixed and stirred at 15000rpm for 20min) to fully swell the montmorillonite. The obtained montmorillonite aqueous dispersion was transferred to a sand mill and ground at 3500rpm and 60rpm for 5h. After grinding for 2h, 10g of stearic acid was added to the system for online modification. The grinding was continued until the average diameter of the montmorillonite particles was 250±20nm to obtain a pre-modified montmorillonite dispersion;

[0049] (2) 1 g KH550 was mixed with 2 g pure water, and hydrolyzed in a constant temperature water bath at 25 °C for 2 h to obtain a silane coupling agent liquid. After heating to 97 °C, 15 g of a calcium chloride / zinc chloride mixture was added and mixed in an oil bath for 1 h to obtain a silane coupling agent / calcium chloride / zinc chloride dispersion;

[0050] (3) blending the silane coupling agent / calcium chloride / zinc chloride dispersion obtained in step (2) and the pre-modified montmorillonite dispersion obtained in step (1), and reacting them in an oil bath at 97° C. for 4 h to obtain a PVC composite thermal stabilizer;

[0051] Preparation of a PVC building material:

[0052] (1) 100 g of PVC resin, 40 g of DINP, 10 g of DOA, 3 g of PVC composite heat stabilizer, 10 g of tricresyl phosphate, and 1 g of UV-531 were mixed and beaten to obtain PVC paste resin; the viscosity of the obtained PVC paste resin was adjusted to a viscosity of 1500 mpa.s on a machine using a viscosity reducer D80 to obtain PVC slurry;

[0053] (2) The PVC slurry and mesh prepared in step (1) are dipped and coated by the roller of a coating machine. After coating, the PVC slurry and mesh are fused with the PVC film at a high temperature of 180° C. to obtain a PVC coated product (i.e., PVC building material, which can be used as PVC architectural membrane material).

[0054] Example 3: Preparation of a novel PVC composite heat stabilizer and PVC building materials

[0055] Preparation of a new type of PVC composite heat stabilizer:

[0056] (1) 5g of sodium montmorillonite and 95g of pure water were fully mixed and emulsified by an emulsifier to obtain a montmorillonite aqueous dispersion (mixed and stirred at 15000rpm for 20min) to fully swell the montmorillonite. The obtained montmorillonite aqueous dispersion was transferred to a sand mill and ground at 3500rpm and 60rpm for 5h. After grinding for 2h, 15g of stearic acid was added to the system for online modification. The grinding was continued until the average diameter of the montmorillonite particles was 250±20nm to obtain a pre-modified montmorillonite dispersion;

[0057] (2) 1 g KH550 was mixed with 2 g pure water, and hydrolyzed in a constant temperature water bath at 25 °C for 2 h to obtain a silane coupling agent liquid. The mixture was heated to 95 °C and then added with 15 g of a calcium chloride / zinc chloride mixture and mixed for 4 h to obtain a silane coupling agent / calcium chloride / zinc chloride dispersion.

[0058] (3) blending the silane coupling agent / calcium chloride / zinc chloride dispersion obtained in step (2) and the pre-modified montmorillonite dispersion obtained in step (1), and reacting them in an oil bath at 97° C. for 4 h to obtain a PVC composite thermal stabilizer;

[0059] Preparation of a PVC building material:

[0060] (1) 100 g of PVC resin, 40 g of DINP, 10 g of DOA, 3 g of PVC composite heat stabilizer, 10 g of tricresyl phosphate, and 1 g of UV-531 were mixed and beaten to obtain PVC paste resin; the viscosity of the obtained PVC paste resin was adjusted to a viscosity of 1500 mpa.s on a machine using a viscosity reducer D80 to obtain PVC slurry;

[0061] (2) The PVC slurry and mesh prepared in step (1) are dipped and coated by the roller of a coating machine. After coating, the PVC slurry and mesh are fused with the PVC film at a high temperature of 180° C. to obtain a PVC coated product (i.e., PVC building material, which can be used as PVC architectural membrane material).

[0062] Example 4: Preparation of a novel PVC composite heat stabilizer and PVC building materials

[0063] Preparation of a new type of PVC composite heat stabilizer:

[0064] (1) 5g of sodium montmorillonite and 95g of pure water were fully mixed and emulsified by an emulsifier to obtain a montmorillonite aqueous dispersion (mixed and stirred at 20000rpm for 10min) to fully swell the montmorillonite. The obtained montmorillonite aqueous dispersion was transferred to a sand mill and ground at 3000rpm and 50rpm for 6h. After grinding for 3h, 10g of stearic acid was added to the system for online modification. The grinding was continued until the average diameter of the montmorillonite particles was 230±20nm to obtain a pre-modified montmorillonite dispersion;

[0065] (2) Mix 2g KH550 with 2g pure water, hydrolyze in a constant temperature water bath at 30°C for 2h to obtain a silane coupling agent liquid, heat to 95°C in an oil bath, add 15g of a calcium chloride / zinc chloride mixture and mix for 2h to obtain a silane coupling agent / calcium chloride / zinc chloride dispersion;

[0066] (3) blending the silane coupling agent / calcium chloride / zinc chloride dispersion obtained in step (2) and the pre-modified montmorillonite dispersion obtained in step (1), and reacting them in an oil bath at 95° C. for 2 h to obtain a PVC composite thermal stabilizer;

[0067] Preparation of a PVC building material:

[0068] (1) 100 g of PVC resin, 40 g of DINP, 10 g of DOA, 2 g of PVC composite heat stabilizer, 10 g of tricresyl phosphate, and 1 g of UV-531 were mixed and beaten to obtain PVC paste resin; the viscosity of the obtained PVC paste resin was adjusted to a viscosity of 1500 mpa.s on a machine using a viscosity reducer D80 to obtain PVC slurry;

[0069] (2) The PVC slurry and mesh prepared in step (1) are dipped and coated by the roller of a coating machine. After coating, the PVC slurry and mesh are fused with the PVC film at a high temperature of 180° C. to obtain a PVC coated product (i.e., PVC building material, which can be used as PVC architectural membrane material).

[0070] Example 5: Preparation of a novel PVC composite heat stabilizer and PVC building materials

[0071] Preparation of a new type of PVC composite heat stabilizer:

[0072] (1) 5g of sodium montmorillonite and 75g of pure water were fully mixed and emulsified in an emulsifier to obtain a montmorillonite aqueous dispersion (mixed and stirred at 10000rpm for 30min) to fully swell the montmorillonite. The obtained montmorillonite aqueous dispersion was transferred to a sand mill and ground at 4000rpm and 80rpm for 4h. After grinding for 2h, 20g of stearic acid was added to the system for online modification. The grinding was continued until the average diameter of the montmorillonite particles was 270±20nm to obtain a pre-modified montmorillonite dispersion;

[0073] (2) 1 g KH550 was mixed with 2 g pure water, and hydrolyzed in a constant temperature water bath at 20 °C for 4 h to obtain a silane coupling agent liquid. After heating to 92 °C, 20 g of a calcium chloride / zinc chloride mixture was added and mixed for 4 h to obtain a silane coupling agent / calcium chloride / zinc chloride dispersion;

[0074] (3) blending the silane coupling agent / calcium chloride / zinc chloride dispersion obtained in step (2) and the pre-modified montmorillonite dispersion obtained in step (1), and reacting them in an oil bath at 90° C. for 4 h to obtain a PVC composite heat stabilizer;

[0075] Preparation of a PVC building material:

[0076] (1) 100 g of PVC resin, 40 g of DINP, 30 g of DOA, 4 g of PVC composite heat stabilizer, 15 g of triphenyl phosphate, and 3 g of UV-531 were mixed and beaten to obtain PVC paste resin; the viscosity of the obtained PVC paste resin was adjusted to a viscosity of 2000 mPa.s on a machine using a viscosity reducer D80 to obtain PVC slurry;

[0077] (2) The PVC slurry and mesh prepared in step (1) are dipped and coated by the roller of a coating machine. After coating, the PVC slurry and mesh are fused with the PVC film at a high temperature of 180° C. to obtain a PVC coated product (i.e., PVC building material, which can be used as PVC architectural membrane material).

[0078] Comparative Example 1: Preparation of a novel PVC composite heat stabilizer and PVC building materials

[0079] Preparation of PVC heat stabilizer:

[0080] (1) 5g of sodium montmorillonite and 95g of pure water were fully mixed and emulsified by an emulsifier to obtain a montmorillonite aqueous dispersion (mixed and stirred at 15000rpm for 20min) to fully swell the montmorillonite. The obtained montmorillonite aqueous dispersion was transferred to a sand mill and ground at 3500rpm and 60rpm for 5h until the average diameter of the montmorillonite particles was 250±20nm to obtain a montmorillonite dispersion; 15g of a calcium chloride / zinc chloride mixture was added to the montmorillonite dispersion to obtain a mixed heat stabilizer dispersion.

[0081] Preparation of PVC building materials:

[0082] (1) 100 g of PVC resin, 40 g of DINP, 10 g of DOA, 3 g of mixed heat stabilizer dispersion, 10 g of tricresyl phosphate, and 1 g of UV-531 were mixed and beaten to obtain PVC paste resin; the viscosity of the obtained PVC paste resin was adjusted to a viscosity of 1500 mPa.s on a machine using a viscosity reducer D80 to obtain PVC slurry;

[0083] (2) The PVC slurry and mesh prepared in step (1) are dipped and coated by the roller of a coating machine. After coating, the PVC slurry and mesh are fused with the PVC film at a high temperature of 180° C. to obtain a PVC coated product (i.e., PVC building material, which can be used as PVC architectural membrane material).

[0084] Comparative Example 2: Preparation of a new type of PVC composite heat stabilizer and PVC building materials

[0085] Preparation of PVC heat stabilizer:

[0086] (1) 5g of sodium montmorillonite and 95g of pure water were fully mixed and emulsified by an emulsifier to obtain a montmorillonite aqueous dispersion (mixed and stirred at 15000rpm for 20min) to fully swell the montmorillonite. The obtained montmorillonite aqueous dispersion was transferred to a sand mill and ground at 3500rpm and 60rpm for 5h. After grinding for 2h, 10g of stearic acid was added to the system for online modification. The grinding was continued until the average diameter of the montmorillonite particles was 250±20nm to obtain a modified montmorillonite dispersion. 15g of calcium chloride / zinc chloride mixture was added to the modified montmorillonite dispersion to obtain a mixed heat stabilizer dispersion.

[0087] Preparation of PVC building materials:

[0088] (1) 100 g of PVC resin, 40 g of DINP, 10 g of DOA, 3 g of mixed heat stabilizer dispersion, 10 g of tricresyl phosphate, and 1 g of UV-531 were mixed and beaten to obtain PVC paste resin; the viscosity of the obtained PVC paste resin was adjusted to a viscosity of 1500 mPa.s on a machine using a viscosity reducer D80 to obtain PVC slurry;

[0089] (2) The PVC slurry and mesh prepared in step (1) are dipped and coated by the roller of a coating machine. After coating, the PVC slurry and mesh are fused with the PVC film at a high temperature of 180° C. to obtain a PVC coated product (i.e., PVC building material, which can be used as PVC architectural membrane material).

[0090] Comparative Example 3: Preparation of a new type of PVC composite heat stabilizer and PVC building materials

[0091] Preparation of PVC heat stabilizer:

[0092] (1) 5g of sodium montmorillonite and 95g of pure water were fully mixed and emulsified by an emulsifier to obtain a montmorillonite aqueous dispersion (mixed and stirred at 15000rpm for 20min) to fully swell the montmorillonite. The obtained montmorillonite aqueous dispersion was transferred to a sand mill and ground at 3500rpm and 60rpm for 5h until the average diameter of the montmorillonite particles was 250±20nm, thereby obtaining a montmorillonite dispersion;

[0093] (2) 1 g KH550 was mixed with 2 g pure water, and hydrolyzed in a constant temperature water bath at 25°C for 2 h to obtain a silane coupling agent liquid; after heating to 95°C, 15 g of a calcium chloride / zinc chloride mixture was added and mixed to obtain a silane coupling agent / calcium chloride / zinc chloride dispersion;

[0094] (3) blending the silane coupling agent / calcium chloride / zinc chloride dispersion obtained in step (2) and the montmorillonite dispersion obtained in step (1), and reacting them in an oil bath at 97° C. for 4 h to obtain a silane coupling agent-modified montmorillonite dispersion;

[0095] Preparation of PVC building materials:

[0096] (1) 100 g of PVC resin, 40 g of DINP, 10 g of DOA, 3 g of silane coupling agent modified montmorillonite dispersion, 10 g of tricresyl phosphate, and 1 g of UV-531 were mixed and beaten to obtain PVC paste resin; the viscosity of the obtained PVC paste resin was adjusted to a viscosity of 1500 mPa.s on a machine using a viscosity reducer D80 to obtain PVC slurry;

[0097] (2) The PVC slurry and mesh prepared in step (1) are dipped and coated by the roller of a coating machine. After coating, the PVC slurry and mesh are fused with the PVC film at a high temperature of 180° C. to obtain a PVC coated product (i.e., PVC building material, which can be used as PVC architectural membrane material).

[0098] Product performance measurement:

[0099] The product performance was tested on the products of Examples 1-5 and Comparative Examples 1-3, and the testing conditions were the same.

[0100] The bubbles were observed using a polarizing microscope:

[0101] Testing method for bubbles on the product surface: Adjust the focal length under the field of view of the eyepiece 10x and the objective lens 5x until the inside of the product is blurred and the surface of the product is clear, then observe the bubbles on the product surface;

[0102] Testing method for bubbles inside the product: Adjust the focus under the field of view of the eyepiece 10x and the objective lens 5x until the inside of the product is clear and the surface of the product is blurred, then observe the bubbles on the surface of the product;

[0103] Bubble quantity characterization standard: every 50 bubbles in the 0.5*0.5mm field of view is a "+".

[0104] Table 1 Bubble situation of products observed by polarizing microscope (surface and inside)

[0105]

[0106] Simulated UV aging product performance test:

[0107] Simulated UV aging test method: Set the UV aging chamber conditions according to ASTM G154 cycle1 standard, and conduct the test for a total of 2500 hours. Then compare the test sample with the original sample to obtain the color value of the product after 2500 hours of simulated UV aging.

[0108] Table 2 2500h simulated UV aging product color value (Lab color model)

[0109]

[0110] Product mechanical properties test:

[0111] Product mechanical properties test method: According to the national standard GB-T10401, the product mechanical properties are tested using a peel strength tester, a tensile strength tester, and a tear strength tester.

[0112] Table 3 Mechanical properties of sample products

[0113]

[0114] Table 1 shows the bubble situation of each sample under a polarizing microscope. The bubbles of the products of Examples 1-5 are significantly reduced, indicating that the generation of HCl gas byproducts of the products is significantly suppressed, the thermal stability is improved, the product quality is improved, and the "zinc burning" phenomenon of traditional products is significantly improved. Table 2 shows the color difference results of the simulated ultraviolet aging test of each sample. The color difference of the products of Examples 1-5 is smaller than that of the comparative example product, indicating that the anti-ultraviolet aging performance of the products is greatly improved and is more suitable for PVC building materials. Table 3 shows the peel strength, tensile strength, and tear strength of each sample. The peel strength, tensile strength, and tear strength of the products of Examples 1-5 are all better than those of the comparative example product.

[0115] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be noted that for those of ordinary skill in the art, without departing from the basic principles of the present invention, several improvements and modifications may be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The above description of the disclosed embodiments enables professionals and technicians in this field to implement or use the present invention. The various modifications to these embodiments will be obvious to professionals and technicians in this field, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a PVC composite heat stabilizer, characterized in that: The PVC composite heat stabilizer is made of montmorillonite, stearic acid, calcium chloride, zinc chloride, and a silane coupling agent, and the preparation method thereof comprises the following steps: S1: montmorillonite is dispersed and swelled with purified water to obtain a montmorillonite dispersion; the montmorillonite dispersion is ground, stearic acid is added during the grinding, and the grinding is performed to obtain a pre-modified montmorillonite dispersion; S2: taking a silane coupling agent and adding pure water to hydrolyze it to obtain a silane coupling agent liquid; The silane coupling agent liquid is heated, and the calcium chloride / zinc chloride mixture is added and blended to obtain a silane coupling agent / calcium chloride / zinc chloride dispersion; S3: Blending the silane coupling agent / calcium chloride / zinc chloride dispersion and the pre-modified montmorillonite dispersion, heating and reacting to obtain a PVC composite heat stabilizer; In the step S1, the montmorillonite is ground to an average particle size of 200nm-400nm; in the step S2, the hydrolysis temperature is 20°C-30°C, and the hydrolysis time is 2h-4h; in the step S2, the silane coupling agent liquid is heated to 90°C-100°C and the calcium chloride / zinc chloride mixture is added for blending; in the step S3, the heating reaction temperature is 90°C-100°C, and the reaction time is 2h-4h; The montmorillonite is sodium montmorillonite; In step S1, the amount of stearic acid added is 1 to 4 times that of montmorillonite, calculated by weight ratio; In step S2, the total amount of calcium chloride and zinc chloride added is 1 to 4 times that of montmorillonite, calculated by weight ratio; In step S2, the amount of the silane coupling agent added is 0.1 to 0.4 times that of the montmorillonite in parts by weight.

2. The method for preparing a PVC composite heat stabilizer according to claim 1, characterized in that: In the step S1, the montmorillonite is ground to an average particle size of 200 nm to 300 nm.

3. The method for preparing a PVC composite heat stabilizer according to claim 1, characterized in that: In step S2, the silane coupling agent is selected from at least one of KH550 and KH560.

4. A PVC paste resin containing a PVC composite heat stabilizer obtained by the preparation method according to any one of claims 1 to 3, characterized in that: The PVC paste resin contains the following materials: 100 parts by weight of PVC, 30-70 parts by weight of plasticizer, 10-15 parts by weight of liquid flame retardant, 1-3 parts by weight of anti-ultraviolet agent, and 1-4 parts by weight of PVC composite heat stabilizer.

5. The PVC paste resin according to claim 4, characterized in that: The preparation method of the PVC paste resin comprises the following steps: mixing PVC, a plasticizer, a liquid flame retardant, an anti-ultraviolet agent and a PVC composite heat stabilizer, and stirring to obtain the PVC paste resin.

6. The PVC paste resin according to claim 4, characterized in that: The plasticizer is selected from at least one of DINP, DOTP, DOP and DOA.

7. The PVC paste resin according to claim 4, characterized in that: The liquid flame retardant is at least one selected from tricresyl phosphate, tolylene diphenyl phosphate, and triphenyl phosphate.

8. The PVC paste resin according to claim 4, characterized in that: The anti-ultraviolet agent is selected from at least one of UV-531 and UV-9.

9. A PVC building material prepared by using the PVC paste resin according to claim 4, characterized in that: The preparation method of the PVC building material comprises the following steps: Take PVC paste resin and add viscosity reducer to adjust the viscosity on the machine to obtain PVC slurry; dip the PVC slurry and polyester substrate through the roller of the coating machine for slurry coating; after the slurry coating is completed, heat and fuse it with the PVC film to obtain PVC building materials.

10. The PVC building material according to claim 9, characterized in that: The polyester substrate is polyester woven fabric; the viscosity reducer is at least one of the D series solvent oils.

11. The PVC building material according to claim 9, characterized in that: The viscosity of the PVC slurry on the machine is 1000mpa.s~2000mpa.s.

Citation Information

Patent Citations

  • Composite PVC heat stabilizer and preparation method thereof

    CN112724558A

  • PVC (polyvinyl chloride) coated fabric paste and preparation method thereof

    CN102926199A

  • Heat stabilizer used for PVC plastic and production method thereof

    CN109851954A

  • Low-viscosity calcium carbonate filled PVC paste resin, preparation method thereof and preparation method of PVC coated product

    CN117720790A